Analisis Risiko Keselamatan dan Kesehatan Kerja Konstruksi Bangunan Gedung dengan Tahap HIRADC - Ni Kadek Sri Ebtha Yuni; I Nyoman Suardika; I Wayan Sudiasa (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2021)
One of the risks that occur in construction projects comes from aspects of occupational safety and health. Therefore, it is necessary to identify the risks that may occur and determine controls so that these risks can be minimized. The research was conducted on building construction projects on structural and architectural works. From the research there are 36 risks the level of priority 1 that causes the impact of death and permanent injury, priority level 2 as many as 20 risks that fall into the medium category, and priority level 3 as much as 26 risks that fall into the low and mild category. The main priority sequence of work that must be controlled is basement walls and floor plates, roof, wall, structural columns, reinforced concrete structures for foundations and floors, railing work, swimming pool structures, ceiling work, and door window. These risks are controlled by engineering technique with methods, regulating electric lines, working in good lighting, conducting periodic checks on electrical installations and tools, by providing warning signs, using work shoes, helmets, gloves, safety belt, work shoes.